2019
DOI: 10.1039/c9tc00747d
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient platinum-based emitters for warm white light emitting diodes

Abstract: The new compounds [Pt(R-C^C*)(P^P)]PF6 as blue or orange emitters were combined with the red emitter [Pt(bzq)(CN)(CNXyl)] to fabricate two-component WOLEDs and pcWLEDs. They rendered warm white light with optimal CRI and Duv values and a great range of nominal CCT: 4000 K–2000 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 46 publications
6
28
0
Order By: Relevance
“…The X-ray study of 6A , 6B , and 7A (Figures , S56, and S57 and Table ) confirmed their molecular structures showing a really distorted square-planar coordination environment for the metal with C(1)–Pt–C(10) and X(1)–Pt–X(2) (X = P for 6A and 6B , S for 7A ) bite angles of 79°–73°. Regarding the “Pt­(C^C* A/B )” moiety, the Pt–C bond parameters are similar to those of reported platinacycles with N-heterocyclic carbenes, ,,,, and the five-membered platinacycle and the Pt coordination plane result almost coplanar (Table ).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The X-ray study of 6A , 6B , and 7A (Figures , S56, and S57 and Table ) confirmed their molecular structures showing a really distorted square-planar coordination environment for the metal with C(1)–Pt–C(10) and X(1)–Pt–X(2) (X = P for 6A and 6B , S for 7A ) bite angles of 79°–73°. Regarding the “Pt­(C^C* A/B )” moiety, the Pt–C bond parameters are similar to those of reported platinacycles with N-heterocyclic carbenes, ,,,, and the five-membered platinacycle and the Pt coordination plane result almost coplanar (Table ).…”
Section: Resultssupporting
confidence: 81%
“…5 and 1 μs, respectively. Thus, keeping all this in mind and the π-stacked packings reported in the X-ray structure of 7A (Figure S57), the LE band can be attributed to 3 ππ* transitions due to the formation of aggregates as a result of π–π interactions among C^C* groups from adjacent molecules. ,, Considering the analogous emission features (vibronic structure, energy and lifetime) of the HE band with those obtained in 2-MeTHF (10 –5 M, 77 K), it seems reasonable to assume the same emissive origin, 3 ILCT/ 3 MLCT for them.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Having in mind that C,N-cyclometalated compounds with a poor π-acceptor neutral fragment like pyrazole instead of a pyridine would enlarge the energy gap and alter the emissive properties and that the aryl-pyrazole platinum compounds have been barely explored, we decided to expand the investigation to a new synthon N n Bu 4 [Pt­(C^N)­(CN) 2 ] (HC^N = 1-(naphthalen-2-yl)-1 H -pyrazole, 4A ) whose cyclometalated skeleton (Pt­(Naph^N)) also presents structural similarities with the N-heterocyclic carbene species (Pt­(Naph^C*)) we have recently been investigating on. Thus, compound N n Bu 4 ­[Pt­(Naph^N)­(CN) 2 ] ( 4A ) and the counterpart, N n Bu 4 ­[Pt­(Naph^C*)­(CN) 2 ] (HC^C*-κC* = 3-methyl-1-(naphthalen-2-yl)-1 H- imidazol-2-ylidene, 4B ), recently published by Kato and co-workers, have been reacted with TlPF 6 to afford neutral extended structures containing Pt–Tl dative bonds, [PtTl­(Naph^E)­(CN) 2 ] (E = pyrazole 5A , carbene 5B ). Structural and photophysical comparative analyses have been performed regarding the cyclometalated Pt­(Naph^E) motif.…”
Section: Introductionmentioning
confidence: 99%